ANTENATAL CARE (ANC) VISIT FREQUENCY IN THE THIRD TRIMESTER AND PRETERM EVENTS IN PUSKESMAS PONDOH AND JUNTINYUAT IN INDRAMAYU REGENCY BETWEEN 2014-2016 - Elinda Ameliana; Donny Nauphar; Ruri Eka Maryam (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: World Health Organization (WHO) estimates that 15 million babies are born preterm every year and this number continues to increase. Several risk factors for preterm are identified as mother’s lifestyle such as smoking, malnutrition, weight gain during pregnancy, and drug use or other factors such as socioeconomic status. In 2015, WHO reported more than 300.000 women died from pregnancy-related causes and 2.6 million babies were still born worldwide with half occurring during the third trimester. Antenatal Care (ANC) in the third semester aims to identify fetal position and identify complication during pregnancy and screen for pre-eclampsia, infection of the reproductive organs and urinary tract, and plan for delivery. The ANC in the third semester is crucial in keeping pregnant mother healthy throught pregnancy and delivery. Aim: To find out the relationship between third trimester Antenatal Care (ANC) visit frequency and preterm birth event at Puskesmas Pondoh and Juntinyuat in Indramayu regency between 2014-2016. Methods: This was observational analytic study with cross-sectional approach. The sampling technique in this research was done by total sampling with 100 respondens. Data were collected from maternal cohort book and control card of pregnant women. The data were analyzed using Chi-square test and Prevalence Ratio. Results: This study found that the proportion of pregnant mothers with insufficient third trimester ANC was 38% and the number of mothers delivering preterm baby was 32%. Statistical analysis showed that there was a statistical significance between third trimester ANC visit frequency and preterm labor with p=0,000 (p<0,05) and women with insufficient ANC visit have 40 times higher risk of preterm baby compared to mothers who has sufficient ANC visit (PR=40,60; CI95%=11.699-140.8862) in Puskesmas Pondoh and Juntinyuat Indramayu District 2014-2016. Conclusion: Having less than 4 ANC visit in the third trimester may increase the risk of delivering preterm babies. Pregnant women are advised to do ante natal care monthly of a minimum 4 times during the third trimester.